Deficiency of Cardiac Natriuretic Peptide Signaling Promotes Peripartum Cardiomyopathy-Like Remodeling in the Mouse Heart. Issue 7 (18th February 2020) - Otani, Kentaro; Tokudome, Takeshi; Kamiya, Chizuko A.; Mao, Yuanjie; Nishimura, Hirohito; Hasegawa, Takeshi; Arai, Yuji; Kaneko, Mari; Shioi, Go; Ishida, Junji; Fukamizu, Akiyoshi; Osaki, Tsukasa; et al.
Abstract : Background: The maternal circulatory system and hormone balance both change dynamically during pregnancy, delivery, and the postpartum period. Although atrial natriuretic peptides and brain natriuretic peptides produced in the heart control circulatory homeostasis through their common receptor, NPR1, the physiologic and pathophysiologic roles of endogenous atrial natriuretic peptide/brain natriuretic peptide in the perinatal period are not fully understood. Methods: To clarify the physiologic and pathophysiologic roles of the endogenous atrial natriuretic peptide/brain natriuretic peptide–NPR1 system during the perinatal period, the phenotype of female wild-type and conventional or tissue-specific Npr1-knockout mice during the perinatal period was examined, especially focusing on maternal heart weight, blood pressure, and cardiac function. Results: In wild-type mice, lactation but not pregnancy induced reversible cardiac hypertrophy accompanied by increases in fetal cardiac gene mRNAs and ERK1/2 (extracellular signaling-regulated kinase) phosphorylation. Npr1-knockout mice exhibited significantly higher plasma aldosterone level than did wild-type mice, severe cardiac hypertrophy accompanied by fibrosis, and left ventricular dysfunction in the lactation period. Npr1-knockout mice showed a high mortality rate over consecutive pregnancy–lactation cycles. In the hearts of Npr1-knockout mice during or after the lactation period, an increase in interleukin-6 mRNA expression, phosphorylation of signal transducer and activator of transcription 3, and activation of the calcineurin–nuclear factor of the activated T cells pathway were observed. Pharmacologic inhibition of the mineralocorticoid receptor or neuron-specific deletion of the mineralocorticoid receptor gene significantly ameliorated cardiac hypertrophy in lactating Npr1-knockout mice. Anti–interleukin-6 receptor antibody administration tended to reduce cardiac hypertrophy in lactating Npr1-knockout mice. Conclusions: These results suggest that the characteristics of lactation-induced cardiac hypertrophy in wild-type mice are different from exercise-induced cardiac hypertrophy, and that the endogenous atrial natriuretic peptide/brain natriuretic peptide–NPR1 system plays an important role in protecting the maternal heart from interleukin-6–induced inflammation and remodeling in the lactation period, a condition mimicking peripartum cardiomyopathy. Abstract : Supplemental Digital Content is available in the text.